Efficacy of Scalp Cooling in Preventing and Recovering From Chemotherapy-Induced Alopecia in Breast Cancer Patients: The HOPE Study - Kinoshita, Takayuki; Nakayama, Takahiro; Fukuma, Eisuke; Inokuchi, Masafumi; Ishiguro, Hiroshi; Ogo, Etsuyo; Kikuchi, Mari; Jinno, Hiromitsu; Yamazaki, Naoya; Toi, Masakazu (Frontiers in Oncology, 2019)
Purpose: Although scalp cooling devices have been used to prevent chemotherapy induced alopecia in United States and Europe, the efficacy is unknow for Japanese breast cancer patient. We also assess whether scalp cooling device is effective at hair volume recovery at 12 weeks after end of chemotherapy. Methods: Multicenter controlled trial of women with breast cancer patients in Japan undergoing chemotherapy. The study period was from February 2016 through March 2018. The primary endpoint was the proportion of no alopecia at the end of chemotherapy. Secondary endpoints included the hair volume at 12 weeks after end of chemotherapy. Results: Thirty-four (34) patients were allocated to the scalp cooling group and 14 patients were allocated to the control group in a sequential manner. The average age was about 50 years old in both group (Scalp cooling: 50.0±9.6 years, control: 49.0±9.0 years). The breast cancer stage, type of chemotherapy, and chemotherapy regimens were as follows: Stage II at > 50% in both groups (Scalp cooling: 53.1%, controlled: 64.3%), Adjuvant at > 90% (Scalp cooling: 96.9%, control: 92.9%), and TC therapy at > 60% (Scalp cooling: 75.0%, control: 64.3%). Patients who were judged as no alopecia at the end of chemotherapy were 26.7% (8/30) in the scalp cooling and 0% (0/13) in control (P=0.011). The ratio of 50% or higher hair volume (grades 0 or 1) at 12 weeks after end of chemotherapy was 85.7% (24/28) in scalp cooling and 50.0% (6/12), in control. Serious adverse events were observed in 1 event (fever) in 1 patient in the scalp cooling and 4 events (acute gastroenteritis, wound infection, skin rash and cellulitis) in 3 patients in control. A causal relationship was denied in all cases. Conclusions: The scalp cooling demonstrated the prevention of alopecia and safety for Japanese patient. In addition, compared to the control group, scalp cooling resulted in faster recovery in hair volume even in the patient who failed scalp cooling during the chemotherapy.